BILANGAN KETERHUBUNGAN TITIK PELANGI BEBERAPA KELAS GRAF - Ameliyah, Addinda Nur; Budayasa, I Ketut (MATHunesa: Jurnal Ilmiah Matematika, 2023)
A graph G is called a rainbow vertex connected if every two vertices G are connected by a rainbow path, that is, a path whose all the internal vertices are of a different color. The rainbow vertex connection number of graph G denoted by rvc(G) is the minimum number of colors used to color all vertices by G such that the graph G is connected to rainbow vertex. The rainbow vertex connection number in a graph will not be less than the diameter of the graph minus one. The rainbow vertex connection number discussed in this article for various classes of graphs include complete graph Kn, complete bipartite graph Km,n , wheel graph Wn , two-layer wheel graph Wn2, complete multipartite graph Kn1,n2,...,nt , path Pn, comb graph GSn, graph , graph , graph , graph . Keywords: graph, vertex coloring, rainbow vertex connection number.